PENGARUH KETERAMPILAN MENGAJAR GURU TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMPN 2 PROPPO PAMEKASAN - Maliki, Imyal Al; Rijal, Syamsul (Fakultas Agama Islam Universitas Islam Madura, 2024)
Learning motivation is expected to be able to inspire students' enthusiasm for learning so that students can excel, research on teaching skills and learning motivation. This research uses quantitative research using the product moment correlation formula. The results of the research show that at SMPN 2 Proppo Pamekasan it produces: 1) There is an influence of the teaching skills of Islamic Religious Education subject teachers on student learning motivation in motivating students to learn at SMPN 2 Proppo Pamekasan. This is proven by hypothesis testing using the Product Moment formula which obtains 0.468 from N = 76 or df = 74. The result